Cultural Specificities of Succession’ Failure and Success in the Context of Unlisted Moroccan Family-Owned Businesses - Allioui, Azzeddine; Habba, Badr; Azizi, Taib Berrada El (Business Management and Strategy, 2021)
The purpose of this research aims to study the relationship between the cultural specificities of the Moroccan context and the success or failure of succession strategies (in terms of planning and process) in the case of Moroccan unlisted family businesses. Our study covered a sample of 20 unlisted Moroccan family businesses, 8 of which are SMEs, 6 are large firms, and 6 are VSEs, through a qualitative research based on semi-structured interviews with the managers of family businesses. Our results explain the influence of Moroccan cultural specificities on the success or failure of the transfer of family businesses. Indeed, these influences essentially manifest themselves in three antecedents: the succession planning that already reflects the intention to pass on the family business to the next generations, either by having a well-prepared plan, or an absence of a succession plan that leaves things to chance; the succession process that is influenced in part by specificities of Moroccan culture by granting privilege to the eldest male in the succession, and in another part this process becomes more rational by giving credit to successors competent to take over the family business in the case of large family businesses; and cultural constraints that are manifested mainly by the taboos surrounding the death of the predecessor and religious principles that similarly explain the different configurations of success or failure of the succession strategy of the family business. An extension of this work could be a multi-factor analysis in future researches.